RNA Isolation of Dengue Virus Type 2 with Different Precipitation Solvents : Methanol, Chloroform, and 2-Isopropanol. - Yovilianda Maulitiva Untoro; Teguh Hari Sucipto; Harsasi Setyawati; Siti Churrotin; Ilham Harlan Amarullah; Puspa Wardhani; Aryati Aryati; Shuhai Ueda; Soegeng Soegijanto (Jurnal Kimia Riset, 2018)
Dengue virus distributed in tropical and subtropical regions in the world. DENV viruses are transmitted between humans primarily by Aedes aegypti and Aedes albopictus mosquitoes and are endemic in most areas in which the vectors occur. Four serotypes of dengue virus are DENV-1, DENV-2, DENV-3 and DENV-4. DENV-2 is comprised of six genotypes. Ethanol precipitation is a commonly used technique for concentrating and de-salting nucleic acids (DNA or RNA) preparations in aqueous solution. RNA isolation by combining Guanidinium thiocyanate and phenol reported has been reported. In this report, we investigated RNA isolation from DENV-2 using QIAamp Mini Kit with 2-Isopropanol, Methanol, Chloroform precipitation solvent. Electrophoregram showed DNA band as  the result of RNA isolation with methanol and 2-isopropanol are produced quite well. Dna band of the of RNA isolation with chloroform solvent has the lowest intensity than methanol and 2-isopropanol. This study showed that methanol and 2-isopropanol  can used as precipitation solvent for isolating RNA.